Enhancing environmental awareness through education on recognizing and conserving flagship and endemic species of Bangka Island in Riding Panjang Village, Bangka Regency - Randi Syafutra; Hendi Hendra Bayu (Universitas Muhammadiyah Magelang, 2024)
Environmental awareness is essential for the conservation of biodiversity, particularly in regions rich in endemic and flagship species, such as Bangka Island. The Community Service (CS) program aimed to enhance environmental awareness among young adults in Riding Panjang Village, Belinyu District, Bangka Regency, Bangka Belitung Islands Province, through education on recognizing and conserving Bangka Island’s flagship and endemic species. This CS program, conducted on August 10th, 2024, included 25 participants aged 18-29 and involved three phases: pretest, education, and posttest. The pretest results revealed that participants had limited prior knowledge, with an average score of 56 points. The educational phase utilized interactive presentations to increase understanding of the species' ecological roles and conservation needs. Following the education, the posttest showed a significant improvement in knowledge, with an average score of 86 points, marking a 30-point increase. These findings demonstrate the effectiveness of structured educational programs in raising awareness and engagement in biodiversity conservation. The results underscore the importance of conservation education, particularly for emerging adults who are more open to new ideas and prepared to adopt social and environmental responsibilities. This CS program successfully increased participants' understanding and motivation to support conservation efforts for Bangka Island’s unique species.